COVID-19: Could Irisin Become the Handyman Myokine of the 21st Century? - Catalano, Alessia (Coronaviruses, 2020)
The ongoing Coronavirus disease 2019 (COVID-19) outbreak in China has become the world's leading health headline and is causing major panic and public concerns. After emerging in the City of Wuhan, China, COVID-19 has spread to several countries becoming a worldwide pandemia. Among the studies on COVID-19, it has been demonstrated that novel coronavirus pneumonia is closely associated with inflammatory storms. Controlling the inflammatory response may be as important as targeting the virus. Irisin is a muscle-contraction-induced immunomodulatory myokine related to physical activity. Irisin drives the “browning” of white adipocytes, so enhancing metabolic uncoupling and hence caloric expenditure. Irisin has been clearly shown to be a handyman molecule by exerting beneficial effects on adipose tissues, pancreas, and bone through “cross-talk” between skeletal muscleadipocyte, skeletal muscle-pancreas, and skeletal muscle-bone, respectively. Irisin has been proposed as a promising strategy for early diagnosis and treatment of various types of cancers, neurological diseases and inflammatory conditions. Irisin has been demonstrated to suppress the immune response, too. The importance of irisin is demonstrated by the increase in the number of scientific papers and patents in recent years. The identification of irisin receptor should greatly facilitate the understanding of irisin’s function in exercise and human health. This review examines the structure and recent advances in activities of irisin, suggesting it for further studies on the prevention and cure of COVID-19. Nowadays, studies on irisin plasma levels and physical activity may be useful tools to further investigate the prevention of COVID-19. Irisin may be suggested as a potential novel intervention for COVID-19 by mitigating inflammatory storms, suppressing the immune response and simultaneously alleviating neurological disorders such as depression and anxiety.
Keywords: diabetes